Male breast cancer: a 5-year experience from a State Cancer Institute - Pawar, Shashi Singh; Kumar, Manish; Kishor, Kunal; Ahmad, Nadeem; Singh, Sanjeet Kumar; Lata, Kumari Anshu (International Surgery Journal, 2021)
Background: Male breast cancer (MBC) is an uncommon malignancy accounting for <1% of all cancers in men and <1 % of overall breast cancer cases. Although there are many similarities between MBC and female breast cancer (FBC), they are not identical in clinical behaviour. There is need to understand the exact biological behavior of MBC. Methods: A retrospective observational study was done at State Cancer Institute, IGIMS, Patna which included all MBC patients registered during a 5-year study period (January 2016 to April 2021). 16 consecutive cases of MBC were identified and their detailed clinicopathological profile was analyzed. Results: MBC accounted for 1.10% of the total breast cancer cases. The median age of presentation was 58 years. Most common presentation was lump. Invasive ductal carcinoma (IDC) was most common histology. Majority of the patient presented to us in advanced stage. Estrogen receptor (ER)/progesterone receptor (PR) status was found to be positive in 12 patients. HER-2/neu receptor was positive in 4 patients. 2 patients had triple negative disease (TNBC) status. Surgery in the form of modified radical mastectomy (MRM) was done in 10 patients. All patients received adjuvant therapy as per NCCN guidelines. Conclusions: MBC is rare disease presenting at a relatively early age in Indian male patients. Most of them have positive ER/PR status. As outcomes have not improved comparatively, there is a need to evolve separate guidelines for MBC.